Challenging ideological environments: international teachers' experiences in an outside-of-country teacher training programme. Issue 3 (1st September 2016) - Gutierrez, Amanda
Abstract : Teacher training for developing nation contexts is often conducted in short, intensive inside and outside-of-country programmes. Concerns have been raised in relation to the uncritical take-up of the western-centric material provided by these programmes, which are usually funded by national and international government organizations. This paper explores an approach used in an outside-of-country teacher training programme funded by an Australian government grant. The research focused on teacher trainers from the Monastic education system and their reflections on whether critical literacy approaches could be incorporated into curriculum in Myanmar. It used a Bakhtinian framework to analyse the teacher trainers' ideological environments and their hybridizations of critical literacy discourses for their own contexts. It was found that while the teacher trainers were passionate about the worth of developing critical literacy skills for their teachers and pupils, they struggled with a range of constraints that existed for them within their country. The research illustrated the importance of providing spaces for participants in programmes such as these to critically reflect on the relevance of non-government organization (NGO) and international non-government organization (INGO) training programmes, especially in light of the multiple challenges that are a part of their everyday lives.